Implementasi Metode Runtun Waktu dalam Pemodelan Total Harga Alat Kedokteran dan Kesehatan - Daniar Wahyu Laraswati; Achmad Fauzan (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
Hospital is an institution or health service that provides total individual health care by providing outpatient, inpatient, and emergency services. The health services that will be provided are promotive, preventive, and rehabilitative services. One of the efforts to improve the quality of hospital services is to provide good health services. In terms of supporting the health services provided, a health management is needed. The high price of medical supplies and equipment is due to several other factors causing hospitals to be able to make plans in the procurement of medical equipment and hospital medicine. Therefore, the author uses the Autoregressive Moving Average (ARMA) method in this study to predict the Total Price of Medical and Health Equipment Needed at the Sleman Regional General Hospital in the coming period. Based on the analysis that has been found, one significant and best ARMA model is obtained with the AIC value of 223.92 with equation and the MAPE value of 18.78%, which means the accuracy of the forecasting is 81.22%.